ASME 2022 ICE Forward Conference 2022
DOI: 10.1115/icef2022-90452
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ethanol Addition on the Laminar Burning Velocity of Gasoline Surrogates With Toluene

Abstract: Laminar burning velocity (LBV) is a crucial parameter in many practical combustion simulations, and the acquisition of LBVs is a critical step for evaluating potential alternative fuels and/or suitable surrogates. Ethanol is regarded as one of the most promising alternative fuels, particularly for spark ignition engines, as it may be produced from renewable biomass. While there exists data showing the pressure dependence on ethanol’s LBV compared to iso-octane and n-heptane (primary reference fuels (PRFs)), th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(63 reference statements)
0
0
0
Order By: Relevance
“…Specif-ically, during the low temperature heat release, the reactivity of ethanol is suppressed but the reactivity of toluene is significantly enhanced [39]. Similar observations have been made when studying the laminar burning velocity of equal-volume binary and ternary mixtures of iso-octane, ethanol, and toluene at 380 K and 450 K [40,41,42]. As Sarathy et al found, in this region, ethanol favours chain termination pathways leading to acetaldehyde [7].…”
Section: Binary Mixturessupporting
confidence: 62%
“…Specif-ically, during the low temperature heat release, the reactivity of ethanol is suppressed but the reactivity of toluene is significantly enhanced [39]. Similar observations have been made when studying the laminar burning velocity of equal-volume binary and ternary mixtures of iso-octane, ethanol, and toluene at 380 K and 450 K [40,41,42]. As Sarathy et al found, in this region, ethanol favours chain termination pathways leading to acetaldehyde [7].…”
Section: Binary Mixturessupporting
confidence: 62%